2018
DOI: 10.1038/s41588-018-0263-0
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid and BMP4 cooperate with p63 to alter chromatin dynamics during surface epithelial commitment

Abstract: Human embryonic stem cell (hESC) differentiation promises advances in regenerative medicine 1 – 3 , yet conversion into transplantable tissues remains poorly understood. Using our keratinocyte differentiation system, we employ a multi-dimensional genomics approach to interrogate the contributions of inductive morphogens retinoic acid (RA) and bone morphogenetic protein 4 (BMP4) and the epidermal master regulator p63 4 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 59 publications
(74 reference statements)
2
40
0
Order By: Relevance
“…The nucleoprotein p63 is widely and selectively expressed in a variety of human tissues, especially in proliferating epithelial tissues [42]. Studies have shown an important role of p63 in skin development, maintenance of an undifferentiated state of stem cells, and stem cell proliferation [43].…”
Section: Keratinmentioning
confidence: 99%
“…The nucleoprotein p63 is widely and selectively expressed in a variety of human tissues, especially in proliferating epithelial tissues [42]. Studies have shown an important role of p63 in skin development, maintenance of an undifferentiated state of stem cells, and stem cell proliferation [43].…”
Section: Keratinmentioning
confidence: 99%
“…These opposite interpretations may indicate that other lineage-determining factors could compensate for p63 function in a p63-null context, whereas mutant p63 in iPSCs abrogates the function of the normal p63. Although p63 is dispensable to drive human embryonic stem cells (hESCs) to differentiate to surface ectoderm progenitor cells, it is required for further differentiation toward functional keratinocytes upon RA/BMP4 treatment [ 60 ]. It has been shown that genes expressed at an early differentiation stage are not under the control of p63.…”
Section: Tp63 In Epidermal Commitment and Differentiationmentioning
confidence: 99%
“…Interestingly, ΔNp63 (−/−) epidermal cells express a number of transcripts associated with embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) and display compromised epithelial identity [ 69 ], suggesting that ΔNp63 exerts repressive role on genes expressed at the early differentiation stage once surface ectoderm progenitor cells enter maturation stage. Mechanistically, p63 reduces chromatin accessibility at morphogen-dependent accessible sites through promoting deposition of H3K27me3 at these sites during the maturation stage [ 60 ]. These studies consistently highlight that p63 exerts intrinsic pioneer factor activity, to open inaccessible chromatin, and it cooperates with specific TFs during keratinocyte maturation.…”
Section: Tp63 Acts As An Epidermal Pioneer Factor To Open Chromatin Rmentioning
confidence: 99%
“…These molecular characteristics are suggestive of a relatively quiescent, primitive stem/progenitor cell state, a notion supported by its placement as the initial state in the epidermal lineage (this study), and its high expression of Col17a1, which encodes a marker of long-term epidermal stem cells that can outcompete other cells (Liu et al, 2019). The Col17a1 Hi state is enriched for genes such as Trp63, a master regulator of various aspects of epidermal development, including the initial specification from simple epithelia, promotion of stratification, proliferation, as well as terminal differentiation (Li et al, 2019;Mills et al, 1999;Pattison et al, 2018;Truong et al, 2006;Yang et al, 1999). The reduction of basal cells in the Col17a1 Hi state during wound re-epithelization implicates their mobilization in the case of increased demands for cellular outputs.…”
Section: Discussionmentioning
confidence: 77%